2021
DOI: 10.3390/ma14216363
|View full text |Cite
|
Sign up to set email alerts
|

Highly Insulative PEG-Grafted Cellulose Polyurethane Foams—From Synthesis to Application Properties

Abstract: In this paper, native cellulose I was subjected to alkaline treatment. As a result, cellulose I was transformed to cellulose II and some nanometric particles were formed. Both polymorphic forms of cellulose were modified with poly(ethylene glycol) (PEG) and then used as fillers for polyurethane. Composites were prepared in a one-step process. Cellulosic fillers were characterized in terms of their chemical (Fourier transformation infrared spectroscopy) and supermolecular structure (X-ray diffraction), as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…This is because wood exhibits the ability to bind water molecules through the active hydroxyl groups of cellulose and hemicelluloses [ 63 ]. This is confirmed by studies conducted, among others, by Grząbka-Zasadzińska et al [ 54 ], in which cellulose filler was used to produce PUR foam before and after poly(ethylene glycol) modification. Such an increase in water absorption was also observed when PUR foam was modified with cinnamon or coffee [ 30 , 64 ].…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…This is because wood exhibits the ability to bind water molecules through the active hydroxyl groups of cellulose and hemicelluloses [ 63 ]. This is confirmed by studies conducted, among others, by Grząbka-Zasadzińska et al [ 54 ], in which cellulose filler was used to produce PUR foam before and after poly(ethylene glycol) modification. Such an increase in water absorption was also observed when PUR foam was modified with cinnamon or coffee [ 30 , 64 ].…”
Section: Resultssupporting
confidence: 72%
“…Such observations are confirmed by the work of other authors. The literature shows that the use of virtually any lignocellulosic filler results in weaker cell structures with a large number of open cells, which significantly affects the final properties of polyurethane composites [ 54 ]. An unfavourable effect of fillers’ admixture on the morphology of PUR foams is attributed to changes in viscosity and concentration of the reaction mixture, as a result of which the formation and growth of cells are inhibited, leading to a heterogeneous structure of foams [ 17 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…N,N-dimethylacetamide (DMA) and Lithium Chloride (purchased by Sigma Aldrich, St. Louis, MO, USA) were used as the reaction solvent and catalyst to solubilize CNCs [ 48 ]. The silane n-butyl-trichlorosilane (TCPS, Sigma Aldrich) was selected as a silane agent.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, both crystal and modified amorphous CNCs through ball-milling were employed within polyurethane foams to partially substitute OH groups of conventional polyols [ 46 , 47 , 48 ], producing a stiff polymer matrix, resulting in fine cell structure [ 46 ] and, in specific cases, improving electrical properties too [ 47 ]. Furthermore, CNCs were modified by means of organic solvents i.e., poly(ethylene glycol) [ 48 ], through silane chemistry. As a result, the obtained composite PURs showed a slight decrease in thermal conductivity and in compressive strength, due to the formation of partial open cells structure in the obtained foams.…”
Section: Introductionmentioning
confidence: 99%
“…It is also worth paying attention to how the structure of PUR foam influences its properties. According to the literature data, the use of lignocellulose filler results in weaker cell structures with a large number of open cells, which significantly affects the final properties of polyurethane composites [ 24 ]. Sung and Kim [ 25 ] found that smaller pore sizes resulted in a smaller distance between the cell walls; thus, the resistance to deformation under the external force increased with the decrease in the size of the cells.…”
Section: Introductionmentioning
confidence: 99%